2019
DOI: 10.1007/s12282-019-00964-5
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Breast cancer cell motility is promoted by 14-3-3γ

Abstract: The correct name of the corresponding author should be ''Takahiro Mimae'', and not ''Emiko Hiraoka'' as given in the original publication of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Consequently, it is causally related with migration and invasion of tumor cells and the presence of metastases. Similarly, to our study, this isoform has already been linked to metastases of breast tumors and its inhibition has reduced the invasiveness of malignant cells [49]. In any case, regardless of the isoform, inhibition of 14-3-3 protein is strongly linked to inhibition of cell proliferation and migration, in addition to stimulating apoptosis [46][47][48].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consequently, it is causally related with migration and invasion of tumor cells and the presence of metastases. Similarly, to our study, this isoform has already been linked to metastases of breast tumors and its inhibition has reduced the invasiveness of malignant cells [49]. In any case, regardless of the isoform, inhibition of 14-3-3 protein is strongly linked to inhibition of cell proliferation and migration, in addition to stimulating apoptosis [46][47][48].…”
Section: Discussionsupporting
confidence: 83%
“…The 14-3-3 protein has ability to bind to oncogenic proteins and therefore its overexpression is highly related to several tumor types, such as breast, prostate, ovaries and lung cancer [47,48]. 14-3-3γ, found in this study, is one of the isoforms already identified in 14-3-3 protein, and is related to cell motility [48,49]. Consequently, it is causally related with migration and invasion of tumor cells and the presence of metastases.…”
Section: Discussionmentioning
confidence: 52%
“…In addition to EMT mediators, DUBs target other molecules involved in cancer invasiveness. High expression of 14-3-3γ is found in various cancers, such as breast cancer and NSCLC [137,138]. Overexpression of 14-3-3γ promotes cell migration and invasion and correlates with the invasiveness of cancer cells.…”
Section: Dubs and Metastasismentioning
confidence: 99%